2011
DOI: 10.1007/s10695-011-9587-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary administration of Echinacea purpurea on growth indices and biochemical and hematological indices in rainbow trout (Oncorhynchus mykiss) fingerlings

Abstract: This study was conducted to evaluate the effects of Echinacea purpurea (EP) on growth and some hematological and blood biochemical indices of rainbow trout fingerlings. A basal diet was supplemented with 0 (control), 0.25, 0.5, 1, and 2 g EP kg⁻¹ to formulate five experimental diets. Each diet was randomly allocated to triplicate groups of fish with an initial average weight of approximately 8 g. After 8 weeks of feeding trial, fish fed diets with 0.25 and 0.5 g EP kg⁻¹ showed highest final weight and SGR and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 17 publications
3
19
0
Order By: Relevance
“…Fish of all replicates were weighed individually, and the indexes were calculated by the following formulas (Oskoii et al . ).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Fish of all replicates were weighed individually, and the indexes were calculated by the following formulas (Oskoii et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…(Grimm & Müller ; Sun, Currier & Miller ; Weber, Taylor, Stoep, Weiss, Standish & Calabrese ; Matthias, Banbury, Bone, Leach & Lehmann ). EP also showed effects on growth promotion and immuno‐regulation in fish culture (Aly, Mohamed & John ; Aly & Mohamed ; Oskoii, Kohyani, Parseh, Salati & Sadeghi ).…”
Section: Introductionmentioning
confidence: 99%
“…In the limited number of researches carried out with the aim of determining the opportunity of using plants and the active agents they contain in the cultivation, it has been reported that plant extracts added to the feed and water enhance the feed consumption, feed conversion, and growth and carcass quality (Simsek et al, 2005;Immanuel et al, 2009;Oskoii et al, 2012). Several studies have reported that oral administration of fig and onion extract in Paralichthys olivaceus (Cho, 2011), fig in Paralichthys olivaceus (Lee et al, 2015) improved growth performance.…”
Section: Introductionmentioning
confidence: 99%
“…Echinacea purpurea (EP) has been shown to have non-specific immunostimulatory properties, including increased phagocytosis, cytokine production (TNFh, IL-1, IL-6 and IL-10), natural killer cell activity, chemotaxis and oxidative burst of either neutrophils or macrophages (Bauer 2002, Stevenson et al 2005, Oskoii et al 2012. The glycoproteins, polysaccharides, caffeic acid derivatives, isobutylamides and alkylamides in EP have been shown to have immunosCorrespondence to: L. Guz, e-mail: leszek.guz@up.lublin.pl, tel.…”
Section: Introductionmentioning
confidence: 99%
“…: +48 81 445 60 50 timulatory activity (Burger et al 1997). In fish, EP has been reported to increase specific growth rate, survival rate, resistance to challenge infection, total and differential white blood cell counts, lysozyme activity, and hematocrit and nitroblue tetrazolium values (Aly and Mohamed 2010, Kasiri et al 2011, Oskoii et al 2012. The effects of Echinacea supplementation on disease resistance have been studied in Nile tilapia (Oreochromis niloticus) (Aly and Mohamed 2010) and in the ornamental fish Poecilia reticulata (Guz et al 2011).…”
Section: Introductionmentioning
confidence: 99%